2015
DOI: 10.1021/la504779h
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties of Nanocrystalline PbS Films Deposited at the Water–Oil Interface: A Study of Atmospheric Aging

Abstract: Nanocrystalline thin films of PbS are obtained in a straightforward reaction by precipitation at the interface between toluene (containing a Pb precursor) and water (containing Na2S). Lead thiobiuret [Pb(SON(CN(i)Pr2)2)2] and lead diethyldithiocarbamate [Pb(S2CNEt2)2] precursors are used. The films are characterized by X-ray diffraction and electron microscopy, revealing typical particle sizes of 10-40 nm and preferred (200) orientation. Synchrotron-excited depth-profiling X-ray photoelectron spectroscopy (XPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 51 publications
8
54
0
Order By: Relevance
“…Similar experiments using colloidal QDs are more challenging, because of the presence of large amounts of organic ligand. However, the basic features of the PbS oxidation reaction determined by Cant et al . are confirmed in our studies on PbS CQDs …”
Section: Studies Of Oxidation and Passivationsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar experiments using colloidal QDs are more challenging, because of the presence of large amounts of organic ligand. However, the basic features of the PbS oxidation reaction determined by Cant et al . are confirmed in our studies on PbS CQDs …”
Section: Studies Of Oxidation and Passivationsupporting
confidence: 88%
“…The question of whether or not the reaction proceeds congruently (with dissolution of Pb and S in equivalent amounts) has been extensively debated . We have been able to resolve this in studies of nanocrystalline thin films of PbS obtained in a straightforward reaction by precipitation at the interface between toluene (containing a Pb precursor, such as lead diethyldithiocarbamate (Pb(S 2 CNEt 2 ) 2 ) and water (containing Na 2 S) . This preparation produces high quality material that is largely free of the organic material that attenuates XPS signals from the inorganic nanocrystals.…”
Section: Studies Of Oxidation and Passivationmentioning
confidence: 99%
“…16,17,30 To date, the only metal sulphides to have been synthesised by the decomposition of single source precursors in a polymer film are CdS, 4,5,32,33 , CuInS 2 , 29 ZnS, 34,35 Bi 2 S 3 , 36 and Sb 2 S 3 . 31 Despite an extensive family of single source precursor molecules used for chemical vapour deposition and nanoparticle synthesis, [37][38][39][40][41][42] relatively few have been investigated within a polymer matrix. Of particular note, metal dithiocarbamate complexes have been widely used as precursors for the synthesis of metal sulfide nanocrystals and thin films but have not been tested with the in situ approach.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been employed routinely for many decades to study the surfaces of nanoparticles used in supported heterogeneous catalysis, and is increasingly being used to measure the properties of nanoparticles used for medical and optoelectronic applications. 13-17 Recent reports have indicated that ion scattering methods, such as low and medium energy ion scattering (LEIS and MEIS) may be employed as a sensitive method for measuring the coating thickness of nanoparticles. 18,19 There are a number of challenges that analysts face when they employ ultra-high vacuum techniques to characterize nanoparticles.…”
Section: Introductionmentioning
confidence: 99%